Early cerebral and intestinal oxygenation in the risk assessment of necrotizing enterocolitis in preterm infants. (April 2019) - Schat, Trijntje E.; van Zoonen, Anne G.J.F.; van der Laan, Michelle E.; Mebius, Mirthe J.; Bos, Arend F.; Hulzebos, Christian V.; Boezen, H. Marike; Hulscher, Jan B.F.; Kooi, Elisabeth M.W.
Abstract: Background and aim: Predicting necrotizing enterocolitis (NEC) might help in preventing its devastating consequences. We aimed to investigate whether early cerebral and intestinal tissue oxygen saturation (rSO2 ) and fractional tissue oxygen extraction (FTOE) predict the onset of NEC. Study design: Prospective observational case-control study. Subjects: Infants with gestational age (GA) <32 weeks were included. For every NEC case we matched two controls based on GA, birth weight (BW), and a patent ductus arteriosus. Outcome measures: Cerebral oxygenation and intestinal oxygenation were prospectively monitored two-hours daily during the first five days after birth and once a week thereafter until five weeks after birth or until NEC developed. We used Kaplan-Meier analyses to determine the ability of near-infrared spectroscopy (NIRS) measurements, including their variability, to predict the development of NEC. Results: We included ten infants (median (range) GA 27.1 (24.6–29.4) weeks, BW 903 (560–1630) grams) who developed NEC at median postnatal day 13 (range: 4–43 days), and 20 matched controls. Infants with cerebral rSO2 <70% within the first 48 h after birth developed NEC significantly more often than infants with cerebral rSO2 ≥70% (odds ratio 9.00 (95% CI 1.33–61.14). Intestinal FTOE was higher in infants who developed NEC compared to controls during the last NIRS measurement at median 2 days (range: 1–7) before NEC onset (median 0.65 vs. 0.44). Conclusions: Cerebral oxygenation monitoring early after birth might be valuable in the risk assessment of NEC development. Additionally, our results suggest that intestinal oxygenation is impaired before the onset of clinical NEC. Highlights: Tissue ischemia is hypothesized to play a putative role in the development of NEC. Lower cerebral oxygenation in the first 2 days after birth was associated with a higher risk for NEC in preterm infants. The clinical usefulness of intestinal NIRS monitoring needs to be investigated further.